No Net Loss of Species Diversity After Prescribed Fires in the Brazilian Savanna - Durigan, Giselda; Pilon, Natashi A. L.; Abreu, Rodolfo C. R.; Hoffmann, William A.; Martins, Marcio; Fiorillo, Bruno F.; Antunes, Alexsander Z.; Carmignotto, Ana Paula; Maravalhas, Jonas B.; Vieira, Jésica; Vasconcelos, Heraldo L. (Frontiers in Forests and Global Change, 2020)
Although savannas are fire-adapted ecosystems, prescribing fire for biodiversity conservation remains controversial at least in some regions where savannas occur. Faced with uncertainty, many decision makers and even scientists are still reluctant to prescribe fire for conservation purposes in fire-prone ecosystems, invoking the precautionary principle. Knowledge gaps on the ideal fire regime, such as how and when to burn, and especially the fear of biodiversity losses, are among the main arguments against fire management applied to remnants of native savanna vegetation. To inform this debate, we assessed the impact of prescribed fires on diversity of plants (different growth forms), ants, frogs, lizards, birds, and small mammals, in savannas and grasslands of the Brazilian Cerrado. We assessed the existing species richness, composition, and abundance in areas subjected to long periods of fire suppression and compared to that observed over a short period after prescribed dry-season fires, within each group of plants and animals. Whenever possible, we carried out separate analyses for grassland and savanna. Burning did not significantly reduce species richness of any of the groups analyzed, but had a positive effect on richness of graminoids in grassland. When analyzed at the species level, abundance of most animal groups did not show consistent responses to fire, except for a decrease in some frog populations in grasslands. Forbs, graminoids and subshrubs increased in abundance after fire in grassland areas, though in savanna areas, abundance of forbs and subshrubs tended to decline after fire. Species composition changed little in response to fire as indicated by low levels of dissimilarity between burned and unburned areas. These results confirm the high resilience of Cerrado biota to fire, as expected for savanna ecosystems in general. Besides, we demonstrate here that the risk of biodiversity losses cannot justify the objections to the use of prescribed fire for conservation purposes in the Cerrado.